OBSERVATION VS. SURGERY IN TRAUMATIC MACULAR HOLE: A CASE REPORT HIGHLIGHTING FUNCTIONAL OUTCOME - Kartika, Amelia Rahmah; Yustiarini, Ima; Prakosa, Ady Dwi; Widjaja, Sauli Ari; Firmansjah, Muhammad; Sasono, Wimbo (International Journal of Retina, 2025)
Introduction: Traumatic macular hole (TMH) is a rare consequence of blunt ocular trauma, often leading to visual impairment. While spontaneous closure is possible, the decision between observation and surgical intervention remains debated. Case Report: A 15-year-old male presented with blurry vision in his left eye two weeks after being punched. Examination revealed a macular hole, choroidal rupture, and vitreous hemorrhage. Optical coherence tomography (OCT) confirmed a full-thickness macular hole. Given the potential for spontaneous closure, a three-month observation period was chosen. Follow-ups showed no improvement in visual acuity or anatomical closure, leading to the decision against surgery. Discussion: While vitrectomy has high anatomical success rates, final visual acuity may not differ significantly between surgically and spontaneously closed holes. Factors such as initial visual acuity, ellipsoid zone integrity, and associated ocular injuries influence functional outcomes. In this case, the presence of choroidal rupture and vitreous hemorrhage supported the decision for conservative management. Conclusion: TMH management should balance anatomical and functional outcomes. Observation is a reasonable approach in select cases, particularly in younger patients with a chance of spontaneous closure. Individualized treatment decisions are essential, considering potential surgical risks and visual prognosis.